Implementation of Handshaking Culture (Mushafahah) in Cultivating Tolerance Among Junior High School Students - Aisida, Sufinatin; Malik, Agus; Lathifah, Lathifah; Sidik, Zam Resa; Nurikan, Nurikan (EDUCATIO : Journal of Education, 2022)
Inculcating the values ​​of tolerance in the school environment can be formulated through the implementation of the learning process and school programs. One of them is through a handshake program (Mushafahah) accompanied by greetings, greetings, smiles, and polite and courteous behavior. However, on the other hand, there are still students who carry out less commendable behavior, for example lying, being late for school, fighting, mocking each other, and lack of enthusiasm for learning. Through descriptive qualitative research methods, the results of this study indicate that first, the implementation of the culture of shaking hands as an effort to form an attitude of tolerance in Buana Waru Middle School students is structured in routine school activities, spontaneous activities, and exemplary. Second, the supporting factors for the implementation of the culture of shaking hands start from the supervision of the school principal, family, discipline and teacher role models, and a conducive educational environment. While the inhibiting factors are the lack of support from some teachers and students in this habituation, the lack of role models for some teachers, and the less active participation of the parents. Third, the impact of the culture of shaking hands as an effort to form an attitude of tolerance in Buana Waru Middle School students can improve the personal quality of students in respecting and appreciating their teachers, as well as ethics in establishing relationships between teachers and students or students with students.